2016
DOI: 10.1016/j.ijpvp.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plastic pre-straining level on the creep deformation, crack initiation and growth behaviour of 316H stainless steel

Abstract: The effects of the material pre-straining level, in the form of plastic pre-compression at room temperature, on the tensile, creep deformation, creep crack initiation and growth behaviour of 316H stainless steel have been examined at 550 °C. Experiments have been performed on the 4%, 8% and 12% pre-compressed specimens and the results are compared with existing data on the pre-compressed material to investigate the change in mechanical response, creep failure, creep crack initiation and growth behaviour of 316… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The processed deformation data were applied as displacement boundary conditions on the cut face. A linear elastic material model was used with Young's modulus, , and Poisson's ratio, , of 205 GPa and 0.29 respectively (Mehmanparast et al, 2016) to determine the residual stresses that existed before sectioning the sample.…”
Section: The Contour Methodsmentioning
confidence: 99%
“…The processed deformation data were applied as displacement boundary conditions on the cut face. A linear elastic material model was used with Young's modulus, , and Poisson's ratio, , of 205 GPa and 0.29 respectively (Mehmanparast et al, 2016) to determine the residual stresses that existed before sectioning the sample.…”
Section: The Contour Methodsmentioning
confidence: 99%
“…This suggests that creep strain is not always equally damaging, the results suggest that for a fixed amount of creep strain, the slower it is accumulated the more damaging it is to the specimen. Previous work on this material has shown that prior plastic loading will lower the creep ductility of a specimen [32], suggesting that the tests conducted at a high load would have failed at a greater creep strain had there not been significant plastic strain at the notch during load up. This further confirms the view that creep strain is less damaging the faster it is accumulated in this material.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown in previous studies [15][16][17][18] that plastic pre-straining significantly reduces the creep ductility of the material, compared to the as-received material state. Further shown in the literature is that the creep crack growth (CCG) behaviour of the pre-compressed 316H stainless steel material is similar to the HAZ specimens which is hypothesised to be due to similar creep deofmration and ductility in the PC and HAZ material states [15].…”
Section: Introductionmentioning
confidence: 93%